ANALISIS PENGARUH KUALITAS INTERAKSI, KUALITAS LINGKUNGAN FISIK, DAN KUALITAS HASIL TERHADAP WORD OF MOUTH PENGGUNA JASA LAPANGAN FUTSAL YANG DIMEDIASI KEPUASAN KONSUMEN (SURVEY PADA KONSUMEN PENGGUNA JASA LAPANGAN FUTSAL CITRA KARTINI PONTIANAK) - B31110123, Johanes Jalung (Jurnal Manajemen Update, 2016)
The purpose of this research is to analyze the effect of interaction quality, physical environment quality, and outcome quality toward word of mouth of Citra Kartini futsal court which is mediated by customer satisfaction. The samples of this research are 200 Citra Kartini futsal court?s customers which have used the service at least 2 times. The data gathered from the questionnaires is analyzed using PLS-SEM technique by using SmartPLS 3.0 software. The data analysis results show that physical environment quality and outcome quality have positive effect and significant toward customer?s satisfaction and word of mouth. In the other hand, interaction quality does not significantly affect customer satisfaction and word of mouth. Customer satisfaction is proven to be the intervening variable towards the relationship between physical environment quality and word of mouth, also towards the relationship between outcome quality and word of mouth. Goodness of Fit index analysis on research model reveal that the research model has big GoF index which is 0,864. Keywords: service quality, interaction quality, physical environment quality, outcome quality, customer satisfaction, word of mouth, PLS-SEM